Recycling and regenerating method for positive electrode material of waste lithium iron phosphate battery, positive electrode material, positive plate, secondary battery and power utilization device
By ball milling and calcining the precursors and other materials in waste lithium iron phosphate batteries, the regenerated lithium iron phosphate positive electrode material is solved, and the existing recycling methods are complex and electrochemical performance is achieved, achieving efficient battery material recycling and electrochemical performance improvement.
Patent Information
- Application Number
- CN202411603203.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
AI Technical Summary
The existing LiFePO4 battery recycling method has the problem of complex operation of liquid phase regeneration method and is prone to secondary pollution, and the electrochemical performance of solid phase regeneration method needs to be further improved.
The regenerated lithium iron phosphate positive electrode material is prepared by ball milling the precursor, lithium source, carbon nanotube and nitrogen source in the waste lithium iron phosphate battery, drying, calcining it in an inert gas, cooling, crushing and sieving it. This method forms a three-dimensional conductive network by adding activated carbon nanotubes and nitrogen sources, which improves the conductivity and ion diffusion coefficient and improves electrochemical performance.
It improves the electrochemical performance of LiFePO4, enhances the conductivity of carbon, promotes the transfer of lithium ions and electrons to the electrode, reduces the internal resistance of the electrode, and realizes efficient recycling and regeneration of waste battery materials.
Smart Images

Figure CN119528101A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a method for recycling positive electrode materials of waste lithium iron phosphate batteries, positive electrode materials, positive electrode sheets, secondary batteries and power-consuming devices. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, electric vehicles and energy storage due to their high energy density, no memory effect, fast charge / discharge rate, good cycle stability, low self-discharge and other characteristics. Lithium iron phosphate (LiFePO4) has become one of the most popular cathodes for lithium-ion batteries due to its low cost, high safety and excellent stability. However, due to the limited lifespan (generally 3-8 years) caused by capacity loss, irreversible phase change and active lithium deposition during use, the widespread use of LiFePO4 batteries will generate a large number of waste batteries. Improper disposal will cause environmental pollution and waste of resources. Therefore, the recycling of waste batteries is of great significance to environmental protection, resource conservation and economic benefits.
[0003] LiFePO4 recovery and treatment methods are mainly divided into liquid phase regeneration method and solid phase regeneration method. Liquid phase regeneration method consumes a lot of chemicals, has a complex operation process, is prone to secondary pollution, produces a lot of wastewater, and is difficult to industrialize; solid phase regeneration method has the advantages of relatively short recovery process, low process requirements, low cost and low energy consumption, and can quickly regenerate scrapped LiFePO4 on a large scale. However, the electrochemical performance of solid phase repaired and regenerated lithium iron phosphate needs to be improved. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, an embodiment of the present invention provides a method for recycling and regenerating positive electrode materials of waste lithium iron phosphate batteries, positive electrode materials, positive electrode sheets, secondary batteries and electrical devices.
[0006] In a first aspect, the present invention proposes a positive electrode material, which is obtained by calcining a dry mixed material in an inert gas and crushing and screening it after cooling, wherein the mixed material includes a precursor, a lithium source, carbon nanotubes and a nitrogen source, and the precursor is recovered from waste lithium iron phosphate batteries.
[0007] Among them, the electrical conductivity and ion diffusion coefficient of LiFePO4 were greatly improved by adding a three-dimensional conductive network composed of activated carbon nanotubes, thereby improving its electrochemical performance.
[0008] Furthermore, the nitrogen source is a nitrogen-containing organic matter with reducing properties.
[0009] The presence of heteroatoms on the carbon surface can effectively enhance the conductivity of carbon and promote the transfer of lithium ions and electrons to the electrode. Nitrogen atoms can provide electron carriers and reduce the band gap, greatly reducing the internal resistance of the electrode, thereby effectively improving the electrochemical performance. Nitrogen doping can increase the electron donating ability and carrier number of carbon, effectively improving the conductivity of carbon.
[0010] Furthermore, the nitrogen source includes one or both of melamine and ethyleneimine.
[0011] In waste batteries, part of LiFePO4 is oxidized to form Fe3O4. Due to the substantial change in chemical valence, the electrochemical performance of LiFePO4 is significantly reduced. By doping with melamine and / or ethyleneimine with a certain reducing property, it is beneficial to convert Fe 3+ Reduction to Fe 2+ .
[0012] In some embodiments, the nitrogen source is a mixture of melamine and ethyleneimine, and the mass ratio of melamine to ethyleneimine is 9: 1. Melamine is a macromolecular substance, and ethyleneimine is a small molecule substance. The two are mixed in a mass ratio of 9: 1. The macromolecular nitrogen source has a high content and weak dispersibility, while the small dispersible nitrogen source has a low content and good dispersion. The nitrogen source is evenly dispersed on the particle surface and fully doped by mixing the two.
[0013] Furthermore, the lithium source includes one or more of lithium carbonate, lithium nitrate, lithium oxalate, and lithium hydroxide.
[0014] In a second aspect, the present invention provides a method for preparing the positive electrode material provided in the first aspect, such as Figure 1 As shown, the following steps are included:
[0015] (a) After discharging the waste lithium iron phosphate battery until it is empty, disassembling it to obtain the positive electrode sheet;
[0016] (b) separating the foil by ultrasonication under solvent conditions, filtering and drying to obtain a precursor;
[0017] (c) ball-milling the precursor, lithium source, carbon nanotubes and nitrogen source under dispersant conditions and drying to obtain a mixed material;
[0018] (d) calcining the mixture under inert gas conditions, and crushing and screening the mixture after cooling to obtain a regenerated lithium iron phosphate positive electrode material.
[0019] In step (a), the waste battery is placed in a NaCl solution to allow it to self-discharge to an empty state, and then the waste battery is disassembled normally to obtain a lithium iron phosphate positive electrode sheet.
[0020] In step (b), the positive electrode sheet is placed in an ultrasonic cleaner, and the aluminum foil and the required lithium iron phosphate material are ultrasonically separated under solvent conditions, and the adhered electrolyte and adhesive are removed at the same time; the precursor is obtained after filtration and drying. The solvent can be one or more of ethanol, butanol, and isopropanol. The use of the solvent ensures the uniformity and solubility of the ultrasound and promotes better peeling of the positive electrode active material from the foil.
[0021] The dispersant is anhydrous ethanol, and it is understood that the dispersant may also be other suitable solvents. The ball milling speed is 300-500 r / min, and the time is 2-6 hours, so as to ensure the particle size and dispersion uniformity. After the ball milling is completed, the mixture is dried at 80-120° C. for 2-4 hours to obtain a dried mixture.
[0022] In step (d), the mixed material is placed under nitrogen conditions and placed in a tubular furnace for heat treatment, and heated at 350-365°C for 3-4 hours in a nitrogen atmosphere; then the temperature is raised to 630-660°C and high-temperature calcined for 10-14 hours; finally, the material is cooled to room temperature, crushed and sieved to obtain a regenerated lithium iron phosphate positive electrode material. The sieving process is to pass the crushed material through a 400-mesh sieve.
[0023] In some embodiments, the inert gas in step (d) is argon.
[0024] The present invention controls the morphology of the regenerated lithium iron phosphate material through mechanical ball milling and heat treatment methods, and the particle size is small and the morphology is uniform, which shortens the diffusion distance, reduces the impedance, and provides excellent electronic conductivity between LiFePO4 particles.
[0025] Furthermore, the mass fraction of the nitrogen source in the mixed material is 2% to 8%.
[0026] In the mixed material, the mass fraction of the nitrogen source can be 2%, 4%, 6%, 8%, or a value within the range of any two values. The addition of the nitrogen source within the appropriate range can improve the electron donating capacity and the number of carriers of the carbon on the surface of lithium iron phosphate, effectively improve the conductivity of the carbon, and thus effectively improve the rate performance of the battery; when too little is added, the positive electrode active electron transmission is weak, the internal polarization is large, and the kinetic performance is poor; when too much is added, the gram capacity of the positive electrode active material is low.
[0027] Furthermore, the mass fraction of the carbon nanotubes in the mixed material is 2% to 6%.
[0028] In the mixed material, the mass fraction of carbon nanotubes can be 2%, 3%, 4%, 5%, 6%, or a value within a range consisting of any two values. The amount of carbon nanotubes added within a suitable range can be fully and evenly coated on the surface of lithium iron phosphate to improve the conductivity of lithium iron phosphate; when too little is added, the carbon layer is not fully coated, the electron conduction is poor, and secondly, the iron in the lithium iron phosphate is easy to precipitate, and the battery capacity is reduced; when too much is added, the carbon layer is too thick, which prolongs the electron transmission path, and secondly, the carbon layer is easily damaged during the cycle, and the capacity is low.
[0029] In a third aspect, the present invention proposes a positive electrode sheet obtained by coating a positive electrode slurry including the positive electrode material proposed in the first aspect or the positive electrode material prepared by the method proposed in the second aspect on an aluminum foil and drying the same.
[0030] In a fourth aspect, the present invention provides a secondary battery comprising the positive electrode sheet provided in the third aspect.
[0031] In a fifth aspect, the present invention provides an electrical device including the secondary battery provided in the fourth aspect.
[0032] Compared with the prior art, the beneficial effects of the present invention are:
[0033] The present invention dopes the Fe in the waste lithium iron phosphate with a reducing nitrogen source. 3+ Reduction to Fe 2+ , which not only improves the capacity of the degraded material, but also effectively enhances the conductivity of carbon and promotes the transfer of lithium ions and electrons to the electrode.
[0034] The three-dimensional conductive network composed of activated carbon nanotubes added in the present invention greatly improves the conductivity and ion diffusion coefficient of LiFePO4, thereby improving its electrochemical performance.
[0035] The preparation process of the invention is simple, the raw materials are easily available, large-scale production can be carried out, industrial waste liquid is small, and it has more economic value than the liquid phase regeneration method. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0037] Figure 1 This is a flow chart of the method for recycling and regenerating the positive electrode material of waste lithium iron phosphate batteries of the present invention;
[0038] Figure 2 This is a scanning electron microscope image of the positive electrode material prepared in Example 1;
[0039] Figure 3This is a graph showing the 0.5C discharge gram capacity data of lithium-ion batteries prepared using the positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 as raw materials. DETAILED DESCRIPTION
[0040] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0041] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0042] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0043] Example 1
[0044] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0045] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0046] Using anhydrous ethanol as a dispersant, the precursor, lithium carbonate, carbon nanotubes and nitrogen source were ball-milled at 400r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor, lithium carbonate and carbon nanotubes was 88:5:5, the mass fraction of the nitrogen source was 2%, and the nitrogen source was a mixture of melamine and ethyleneimine in a mass ratio of 9:1.
[0047] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0048] Example 2
[0049] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0050] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0051] Using anhydrous ethanol as a dispersant, the precursor, lithium carbonate, carbon nanotubes and nitrogen source were ball-milled at 400r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor, lithium carbonate and carbon nanotubes was 88:5:5, the mass fraction of the nitrogen source was 4%, and the nitrogen source was a mixture of melamine and ethyleneimine in a mass ratio of 9:1.
[0052] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0053] Example 3
[0054] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0055] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0056] Using anhydrous ethanol as a dispersant, the precursor, lithium carbonate, carbon nanotubes and nitrogen source were ball-milled at 400r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor, lithium carbonate and carbon nanotubes was 88:5:5, the mass fraction of the nitrogen source was 8%, and the nitrogen source was a mixture of melamine and ethyleneimine in a mass ratio of 9:1.
[0057] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0058] Example 4
[0059] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0060] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0061] Using anhydrous ethanol as a dispersant, the precursor, lithium carbonate, carbon nanotubes and nitrogen source were ball-milled at 400r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor, lithium carbonate and nitrogen source was 88:5:2, the mass fraction of carbon nanotubes was 2%, and the nitrogen source was a mixture of melamine and ethyleneimine in a mass ratio of 9:1.
[0062] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0063] Example 5
[0064] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0065] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0066] Using anhydrous ethanol as a dispersant, the precursor, lithium carbonate, carbon nanotubes and nitrogen source were ball-milled at 400r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor, lithium carbonate and nitrogen source was 88:5:2, the mass fraction of carbon nanotubes was 6%, and the nitrogen source was a mixture of melamine and ethyleneimine in a mass ratio of 9:1.
[0067] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0068] Comparative Example 1
[0069] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0070] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0071] Using anhydrous ethanol as a dispersant, the precursor and lithium carbonate were ball-milled at 400 r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor and lithium carbonate was 88:5.
[0072] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0073] Comparative Example 2
[0074] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0075] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0076] Using anhydrous ethanol as a dispersant, the precursor, lithium carbonate and carbon nanotubes were ball-milled at 400 r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor, lithium carbonate and carbon nanotubes was 88:5:5.
[0077] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0078] Comparative Example 3
[0079] The waste batteries are immersed in a 5% by mass NaCl solution to make them self-discharge to an empty state, and then the waste batteries are disassembled normally to obtain lithium iron phosphate positive electrode sheets.
[0080] The lithium iron phosphate positive electrode sheet was placed in an ultrasonic cleaner and an appropriate amount of NMP was added. The aluminum foil and the desired regenerated lithium iron phosphate material were separated at 1000W ultrasonic power for 40 minutes, and the adhered electrolyte and adhesive were removed. The product was filtered and dried at 100°C for 2 hours to obtain the precursor of the desired regenerated lithium iron phosphate composite material.
[0081] Using anhydrous ethanol as a dispersant, the precursor, lithium carbonate and nitrogen source were ball-milled at 400r / min for 5 hours to ensure the particle size and dispersion uniformity. Then, the mixture was dried at 90°C for 3 hours to obtain a dried mixture. The added mass ratio of the precursor, lithium carbonate and nitrogen source was 88:5:2, and the nitrogen source was a mixture of melamine and ethyleneimine in a mass ratio of 9:1.
[0082] The dried mixture was placed under nitrogen conditions and put into a tubular furnace for heat treatment. In a nitrogen atmosphere, it was heated at 355°C for 3 hours, then heated to 650°C and calcined at high temperature for 12 hours; finally, it was cooled to room temperature, crushed, and sieved through a 400-mesh sieve to obtain the regenerated lithium iron phosphate positive electrode material.
[0083] Test Example 1
[0084] The positive electrode material prepared in Example 1 was tested by scanning electron microscopy. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the prepared lithium iron phosphate particles are uniform and have a certain degree of sphericity.
[0085] Test Example 2
[0086] Lithium ion batteries were prepared using the positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3, and their discharge gram capacities were tested respectively. The test results are as follows: Figure 3 And as shown in Table 1.
[0087] The specific preparation process of the lithium-ion battery is as follows: positive electrode: carbon black SP: binder PVDF = 97:1:2 are mixed, solvent NMP is added according to the overall solid content of 62±2%, and the slurry is stirred; the slurry is evenly coated on the foil; baked in a vacuum oven for 1-2 hours, the baking temperature is 100-105°C; the baked electrode is placed in a tableting machine (10-30MPa) for compaction; 5-10 discs are cut out and weighed to screen qualified small discs; TC-CN010 is used as the electrolyte, and assembled into a button battery.
[0088] Table 1:
[0089] serial number 0.5C discharge capacity mAg / h Example 1 149.1 Example 2 151.6 Example 3 148.1 Example 4 147.7 Example 5 148.6 Comparative Example 1 134.3 Comparative Example 2 142.0 Comparative Example 3 138.4
[0090] According to Table 1 and Figure 3 By comparing Examples 1 to 5 with Comparative Examples 1 to 3, it can be seen that when the nitrogen source and the carbon nanotubes are added at the same time, the gram capacity of the prepared lithium ion battery is relatively high.
[0091] By comparing Comparative Examples 1 to 3, it can be seen that when neither the nitrogen source nor the carbon nanotubes are added, the gram capacity of the prepared lithium ion battery is the lowest.
[0092] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0093] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0094] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A positive electrode material, characterized in that: The method is carried out by calcining a dried mixed material in an inert gas, crushing and screening the mixed material after cooling, wherein the mixed material comprises a precursor, a lithium source, carbon nanotubes and a nitrogen source, and the precursor is recovered from waste lithium iron phosphate batteries.
2. The positive electrode material according to claim 1, characterized in that The nitrogen source is a nitrogen-containing organic substance with reducing properties.
3. The positive electrode material according to claim 2, characterized in that The nitrogen source includes one or both of melamine and ethyleneimine.
4. The positive electrode material according to claim 1, characterized in that The lithium source includes one or more of lithium carbonate, lithium nitrate, lithium oxalate and lithium hydroxide.
5. A method for recycling and regenerating waste lithium iron phosphate battery positive electrode materials, characterized in that: The method for preparing the positive electrode material according to any one of claims 1 to 4 comprises the following steps: (a) After discharging the used lithium iron phosphate battery until it is empty, the battery is disassembled to obtain the positive electrode sheet; (b) separating the foil by ultrasonication under solvent conditions, filtering and drying to obtain a precursor; (c) ball-milling the precursor, lithium source, carbon nanotubes and nitrogen source under dispersant conditions and drying to obtain a mixed material; (d) calcining the mixture under an inert gas condition, and crushing and screening the mixture after cooling to obtain a regenerated lithium iron phosphate positive electrode material.
6. The method according to claim 5, characterized in that The mass fraction of the nitrogen source in the mixed material is 2% to 8%.
7. The method according to claim 5, characterized in that The mass fraction of the carbon nanotubes in the mixed material is 2% to 6%.
8. A positive electrode sheet, characterized in that: The positive electrode slurry is obtained by coating the positive electrode material according to any one of claims 1 to 4 or the positive electrode material prepared by the method according to any one of claims 5 to 7 on an aluminum foil and drying the same.
9. A secondary battery, characterized in that: Including the positive electrode sheet as claimed in claim 8.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Repairing and regenerating method of waste lithium iron phosphate battery positive electrode material and application
CN113782857A
Composite positive electrode material and preparation method and application thereof
CN114335461A
Preparation method for regenerating waste lithium iron phosphate positive electrode material based on nitrogen doping
CN116525819A
Method for regenerating positive electrode material of waste lithium ion battery and regenerated positive electrode material
CN118315707A
Anode performance regeneration method for retired power lithium battery, regenerated anode material and application
CN118554051A